Contemporary Sunni-Shia Dynamics: Conflict or Competition? - Ahmad Miftahur Rizki (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2024)
This article delves into the power competition between Saudi Arabia (Sunni) and Iran (Contemporary Shia) by examining their involvement in shaping Middle Eastern influence expansion through fundamentally different ideological approaches, namely Sunni and Shia. The author takes the cases of Syria and Yemen as focal points to narrow down the scope and gauge the efforts of both countries as balancing forces in the Middle East region. The paper adopts an ideological approach to identify conflict patterns and strategies employed by both nations. The objective of this paper is to explore the background of the conflict between these two countries, utilizing ideological approaches to achieve their political goals. Employing a descriptive-analytical approach, this article aims to address the research issues at hand. It reveals that Saudi Arabia and Iran play significant roles in Middle Eastern conflicts, particularly in Syria and Yemen, through various means such as funding and providing military logistical support. The ideological approach is inseparable from the missions carried out by both nations. Iran has succeeded in building alliances with local governments, thus securing victories in Yemen. However, Saudi Arabia, despite employing various alliance-building strategies, has yet to achieve success.